2016
DOI: 10.1002/ima.22154
|View full text |Cite
|
Sign up to set email alerts
|

A fully automatic method for biological target volume segmentation of brain metastases

Abstract: Leksell Gamma Knife is a mini-invasive technique to obtain a complete destruction of cerebral lesions delivering a single high dose radiation beam. Positron Emission Tomography (PET) imaging is increasingly utilized for radiation treatment planning. Nevertheless, lesion volume delineation in PET datasets is challenging because of the low spatial resolution and high noise level of PET images. Nowadays, the biological target volume (BTV) is manually contoured on PET studies. This procedure is time expensive and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 35 publications
0
30
0
Order By: Relevance
“…The proposed method improves and combines two computerassisted and operator-independent methods to segment BTV and GTV from PET [584][585][586] and MR [413,525] images, respectively. Each single method has been already validated [413,584], comparing each of them against the most common literature segmentation methods. The former uses the graph-based RW algorithm [221] and the latter is based on unsupervised FCM clustering [52,53].…”
Section: Multimodal Pet/mri Brain Metastasis Segmentationmentioning
confidence: 99%
“…The proposed method improves and combines two computerassisted and operator-independent methods to segment BTV and GTV from PET [584][585][586] and MR [413,525] images, respectively. Each single method has been already validated [413,584], comparing each of them against the most common literature segmentation methods. The former uses the graph-based RW algorithm [221] and the latter is based on unsupervised FCM clustering [52,53].…”
Section: Multimodal Pet/mri Brain Metastasis Segmentationmentioning
confidence: 99%
“…In medical imaging, especially when dealing with Positron Emission Tomography (PET), the RW method can localise weak edges as part of consistent boundaries. To obtain the Biological Target Volume (BTV) delineation on metabolic PET images, the RW incorporates the PET information, by replacing the pixel intensities with the Standardised Uptake Value (SUV) and computing the arc weights accordingly [30]. In the original method [29], the known nodes are marked by user input, whilst an automatic seed-selection procedure makes the method more reliable [31].…”
Section: Random Walkermentioning
confidence: 99%
“…Further, in the case of brain lesions, as reported in Ref. [16], a fully automatic method can be implemented by taking advantage of the great sensitivity and specificity of MET radiotracers in the discrimination between healthy versus cancer. Hence initial user input, which we require in FDG-PET studies, could be completely avoided in brain studies.…”
Section: Tablementioning
confidence: 99%
“…A typical example is the brain, where high uptake of glucose is a normal condition. It has been reported that the extent of tumour cell invasion in brain metastases can be detected by MET PET even more clearly than by CT or MRI [16,17]. For this reason, we considered MET as an alternative radio-tracer.…”
Section: Introductionmentioning
confidence: 99%